2011
DOI: 10.1007/s10549-011-1578-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral endocrine treatments in women with breast cancer: can it be improved?

Abstract: There is a perception that women on oral endocrine treatments for oestrogen receptor-positive breast cancer will be adherent to these medicines, as they are facing a serious life-threatening disease, and the oral endocrine treatments are effective, easy to use and generally well tolerated. This is not in fact the case, and this is the basis of the first half of this review. The second half is of whether the changes/interventions to 'improve' adherence do actually increase adherence to the oral endocrine medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 61 publications
(121 reference statements)
2
23
0
Order By: Relevance
“…The American Society of Clinical Oncology (ASCO) and National Comprehensive Cancer Network (NCCN) best practice guidelines recommend 5–10 years of adjuvant treatment with oral anti-hormonal medications (also known as hormonal or endocrine therapy) [4–6]. There are two main types of oral anti-hormonal medications: 1) Tamoxifen, a selective estrogen receptor modulator, recommended for both pre- and post-menopausal women; and 2) aromatase inhibitors (e.g., letrozole, anastrozole, exemestane), recommended for post-menopausal women only [7–9]. Regular anti-hormonal medication use is associated with decreased mortality related to cancer recurrence [4,5,1012].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Society of Clinical Oncology (ASCO) and National Comprehensive Cancer Network (NCCN) best practice guidelines recommend 5–10 years of adjuvant treatment with oral anti-hormonal medications (also known as hormonal or endocrine therapy) [4–6]. There are two main types of oral anti-hormonal medications: 1) Tamoxifen, a selective estrogen receptor modulator, recommended for both pre- and post-menopausal women; and 2) aromatase inhibitors (e.g., letrozole, anastrozole, exemestane), recommended for post-menopausal women only [7–9]. Regular anti-hormonal medication use is associated with decreased mortality related to cancer recurrence [4,5,1012].…”
Section: Introductionmentioning
confidence: 99%
“…Side effects vary by medication and can include weight gain, joint pain, hot flashes, headaches, fatigue [19], decreased libido, mild arthritis, vaginal discharge, abdominal bloating, and bone density loss [15]. There is limited evidence regarding the efficacy of strategies for side effect management [9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies assessing rates of adherence to AIs include a large proportion of patients on anastrozole [15,17,18]. In addition, a large cohort study demonstrated adherence to anastrozole in a routine clinical practice setting [12].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Furthermore, among existing insulin users, adherence to the prescribed regimen is suboptimal in up to one third of patients. 10 Failure to initiate insulin therapy in a timely manner and to comply with the recommended injection doses and schedule are key factors that lead to low rates of glycaemic target attainment. Among participants of a multinational study that evaluated the quality of care of patients with diabetes in Asia, more than half of the enrolled patients did not reach the glycated haemoglobin (HbA1c) target of <7.0%, and the situation was worse in those with youngonset diabetes.…”
Section: Psychological Insulin Resistance: Scope Of the Problemmentioning
confidence: 99%